Money market fund vulnerabilities: A global perspective - Antoine Bouveret; Antoine Martin; Patrick E. McCabe (Federal Reserve Bank of New York, 2022)
Money market funds (MMFs) are popular around the world, with over 9 trillion in assets under management globally. From their origins in the 1970s, MMFs have operated in a niche between the capital markets and the banking system, as investment funds that offer private money-like assets with features similar to those of bank deposits. Hence, they are vulnerable to runs that arise from liquidity transformation and from sudden changes in investor perceptions of the funds' ability to serve as moneylike assets. Since 2000, MMF runs have occurred in many countries and under many regulatory regimes. The global pattern of runs and crises shows that MMF vulnerabilities are not unique to a particular set of governing arrangements, and that mitigating these vulnerabilities requires fundamental reforms that either place MMFs more clearly within the investment-fund sector or establish protections for MMFs similar to those for deposits.
Keywords: G20; G23; G28; 330; money market funds; liquidity transformation; runs; nonbank financial institutions; short-term funding markets; information-insensitive assets; financial stability